2007
DOI: 10.1016/j.drugalcdep.2007.04.011
|View full text |Cite
|
Sign up to set email alerts
|

On the development of nicotine dependence in adolescence

Abstract: Little is known about the natural history of drug dependence. This article describes the development and predictors of DSM-IV nicotine dependence in adolescence when tobacco use is initiated. In a two-stage design, a survey was administered to 6th-10th graders in the Chicago Public Schools to select a cohort of adolescents. Household interviews were conducted with adolescents five times and with one parent (predominantly mothers) three times over two years. The analytical sample includes 353 youths, who starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
177
4
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(196 citation statements)
references
References 117 publications
(151 reference statements)
12
177
4
3
Order By: Relevance
“…18 Second, girls seem more prone to early signs of nicotine dependence than boys. 24,25 While a number of studies suggested that initial symptoms of nicotine dependence for youth can appear soon after smoking initiation, [26][27][28] some studies reported that adolescent smokers may show signs of nicotine dependence even when their smoking rates are low and intermittent, 25 with girls developing signs of nicotine dependence more quickly after initiating tobacco use than boys. 24 Therefore, once WP experimentation and initiation has started, never-cigarette smoking girls may develop a cognitive susceptibility faster than their boys' counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…18 Second, girls seem more prone to early signs of nicotine dependence than boys. 24,25 While a number of studies suggested that initial symptoms of nicotine dependence for youth can appear soon after smoking initiation, [26][27][28] some studies reported that adolescent smokers may show signs of nicotine dependence even when their smoking rates are low and intermittent, 25 with girls developing signs of nicotine dependence more quickly after initiating tobacco use than boys. 24 Therefore, once WP experimentation and initiation has started, never-cigarette smoking girls may develop a cognitive susceptibility faster than their boys' counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we examined whether reported reactivity to exposure to SHS in high-risk preteens predicts susceptibility to cigarette smoking. Subjective reactivity to the first smoked cigarette has been shown to predict risk for tobacco dependence 26,43 and to be have some genetic basis. 23,24 Both longitudinal and cross-sectional investigation showed that experiencing SHS as "unpleasant or gross" is protective against smoking susceptibility, suggesting that it may reflect a mechanism for targeted prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, surveys of large nationally representative populations have substantially expanded inclusion criteria for the administration of nicotine dependence items allowing for more careful consideration of the early emerging aspects of dependence Kandel, Hu, Griesler, & Schaffran, 2007).…”
mentioning
confidence: 99%